2018
DOI: 10.1088/1757-899x/288/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield of Chili in Nutrient Film Technique at Different Electrical Conductivity

Abstract: Abstract. An increase production of Capsicum annuum in Nutrient Film Technique (NFT) can be done by setting Electrical Conductivity (EC) of vegetative (Va & Vt) and generative (G) phases. A greenhouse trial has been carried out using a completely randomized design with four treatments and six replications. The treatments were A = EC (Va = 1,2 mS cm -1 , Vt = 2 mS cm ). The result showed that the composition of EC at the initial vegetative (Va) phase 1,5 mS cm -1 , middle vegetative (Vt) phase EC of 2 mS cm -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
2
Order By: Relevance
“…The data from Table 1 showed that an increasing of phosphorus concentration had no effect on plant height at initial stage of vegetative phase due to the plants were still in adaptation to environment and could not absorb the nutrient maximally (Hidayat et al, 2018). The plant began to respond on different phosphorus concentration starting from 5 WAT.…”
Section: Plant Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from Table 1 showed that an increasing of phosphorus concentration had no effect on plant height at initial stage of vegetative phase due to the plants were still in adaptation to environment and could not absorb the nutrient maximally (Hidayat et al, 2018). The plant began to respond on different phosphorus concentration starting from 5 WAT.…”
Section: Plant Heightmentioning
confidence: 99%
“…To meet quantity and quality aspects, this crop cultivation can be done in green house with hydroponic systems (Wu & Kubota, 2008). Hydroponic system in a controlled environment makes production of cherry tomato fruit to be maximum, because management of water and nutrient elements correspond with the needs of the plants (Hidayat et al, 2018). A nutrient solution is delivered at the base of the plant with sufficient volume.…”
Section: Introductionmentioning
confidence: 99%
“…Kendala penerapan teknologi hidroponik di masyarakat diantaranya ketersediaan nutrisi yang masih terbatas distribusinya dan harga nutrisi tanaman yang relatif mahal (Frasetya et al, 2018).…”
Section: Pendahuluanunclassified
“…Nilai Electrical Conductivity (EC) dan pH nutrisi umum digunakan sebagai indikator untuk menghasilkan hasil panen berkualitas (Hidayat et al, 2018). Pengaturan nilai EC selain dapat meningkatkan pertumbuhan tanaman juga merupakan salah satu upaya untuk menghemat kebutuhan nutrisi hidroponik.…”
Section: Pendahuluanunclassified
“…The optimum EC value is significant as a low EC value leads to malnutrition in plants [3]- [7]. In the conventional way of measuring nutrient content, farmers use a handheld EC meter to measure EC values routinely to ensure the EC values are at the optimum range, which is tedious and inconvenient [4]. Furthermore, some farmers only rely on their experience to add fertiliser to nutrient solutions [1], which is sometimes inaccurate and even affects the plant's growth with slight changes in EC value for plants sensitive to EC [8].…”
Section: Introductionmentioning
confidence: 99%